Granting of Loans Cooperative to Members who Affected by Flood (Study in KSP Forma Branch of Cirebon) - Mangirim Limbong; Lathifah Hanim (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2018)
In this research using normative juridical approach reviewing and view and analyze problems based on the principles and the principles of law. Once we examine Cooperative Forma, found the research to solve the problem, namely (1) Cooperative Forma will provide loans conditional on the existence of collateral both objects move or do not move the location of the object collateral is never experienced flooding or close to the river, (2) Cooperative Forma will provide relief penalties and interest for the members of the flooded rice fields or fields that can to repay the loan.Keywords: Cooperatives; Loans; Jams; Natural Factors.